Molecular Characterization of β-Thalassemia in the Czech and Slovak Populations: Mediterranean, Asian and Unique Mutations - Divoká, Martina; Partschová, Martina; Kučerová, Jana; Mojzíková, Renáta; Cermak, Jaroslav; Pospíšilová, Dagmar; Fábryová, Viera; Procházková, Daniela; Indrák, Karel; Divoký, Vladimír (Hemoglobin, 2016)
β-Thalassemia (β-thal) is considered rare in Central Europe. As in other malaria-free regions, the presence of β-thal in Central Europe reflects historical and recent immigration, and demographic changes that have influenced the genetic variability of the current populations living in this area. This study assesses the frequency and spectrum of mutations on the β-globin gene in Czech and Slovak subjects with clinical symptoms of thalassemia. The results of the initial part of this research were published more than two decades ago; the aim of this study was to update these original reports. During the period from 2002 to 2015, 400 cases from Czech and Slovak hematological centers were analyzed. Twenty-nine β-thal mutations, identified in 356 heterozygotes from 218 unrelated families, involve five unique mutations including a recently described insertion of a transposable L1 element into the β-globin gene. One mutation described here is reported for the first time. Most of the mutations were of Mediterranean origin and accounted for 82.0% of cases. All but one case studied were heterozygous carriers, manifesting β-thal minor, with rare exceptions represented by the rare (β(0)) codons 46/47 (+G) (HBB: c.142_142dupG) mutation associated with an α-globin gene quadruplication and by dominantly inherited β-thal with a more severe phenotype. One double heterozygous β-thal patient was a recent immigrant from Moldavia. The list of δβ-thal alleles (26 carriers, 16 families) contains Hb Lepore and two types of δβ(0)-thal deletions. In the past, genetic drift and migration as well as recent immigrations were responsible for the introduction of Mediterranean alleles, while several mutations described in single families were of local origin.
Keywords: běloši; molekulární epidemiologie; Genetic Drift; Heterozygote; beta-globiny; Česká republika; beta-Thalassemia; Pedigree; rodokmen; mutace; genetický drift; Czech Republic; emigrace a imigrace; beta-Globins; Slovakia; Asian People; Slovenská republika; Mutation; Humans; Molecular Epidemiology; Emigration and Immigration; beta-talasemie; frekvence genu; White People; Gene Frequency; Asijci; lidé; heterozygot